A tailored approach to building specialized surgical oncology capacity: Early experiences and outcomes in Malawi - Lameck Chinula; Michael Hicks; Grace Chiudzu; Jennifer H. Tang; Satish Gopal; Tamiwe Tomoka; James Kachingwe; Leeya Pinder; Maya Hicks; Vikrant Sahasrabuddhe; Groesbeck Parham (Elsevier, 2018)
Objectives: Cervical cancer can often be cured by surgery alone, if diagnosed and treated early. However, of the cancer patients who live in the world's poorest countries less that 5% have access to safe, effective and timely cancer surgery. We designed a novel, competency-based curriculum to rapidly build surgical capacity for the treatment of cervical cancer. Here we report experiences and early outcomes of its implementation in Malawi. Methods: Curriculum implementation consisted of preoperative evaluation of patients and surgical video review, discussion of surgical instruments and suture material, deconstruction of the surgical procedure into critical subcomponents including trainees walking through the steps of the procedure with the master trainers, high-volume surgical repetition over a short time interval, intra-operative mentoring, post-operative case review, and mental narration. This was preceded by self-directed learning and followed by clinical mentorship through electronic communication and quarterly on-site visits. Results: Between June 2015-June 2017, 28 patients underwent radical abdominal hysterectomy with bilateral pelvic lymphadenectomy. The first 8 surgeries were performed over 5 days. After the 7th case the trainee could perform the procedure alone. During and between quarterly mentoring-visits the trainee independently performed the procedure on 20 additional patients. Major surgical complications were rare. Conclusions: Life-saving surgical treatment for cervical cancer is now available for the first time, as a routine clinical service, in Central/Northern, Malawi. Keywords: Cervical cancer, Radical hysterectomy, Pelvic lymphadenectomy, Competency-based surgical training